Determinants of uptake of first dose of intermittent preventive treatment among pregnant women in a secondary health Centre in Maiduguri, Nigeria - Balami, Ahmed Dahiru; Md Said, Salmiah; Mohd. Zulkefli, NorAfiah; Bachok, Norsa'adah; Audu, Bala (BioMed Central, 2020)
Background: Studies on uptake of first dose of intermittent preventive treatment in pregnancy (IPTp) are lacking, despite it being a predictor of subsequent doses. This study aimed at assessing the determinants of uptake of first dose of IPTp among pregnant women at the State Specialist Hospital, Maiduguri. Methods: A cross-sectional study was conducted, in which respondents were selected using a systematic random sampling method, and structured questionnaires were used to obtain information from them. Chi-squared test was used to determine factors associated with uptake of first IPTp dose, while a further multivariate logistic regression was performed to determine its predictors. Results: Three hundred and eighty respondents answered the survey, whose ages ranged from 15 to 45 years, and 86.8% were multigravid. Sixty five percent of them were aware of IPTp, and 34.7% believed that IPTp could be harmful to their pregnancies. Over a half of the respondents (52.9%) believed that taking all their IPTp medicines was very good for their pregnancies, while 45.0% felt that taking their IPTp medicines was very pleasant. Only two respondents (0.5%) stated that it was very untrue that their significant others thought that they should take all their IPTp medicines. Half of the respondents said it was very easy for them to take all their IPTp medicines even if they were experiencing mild discomforts while taking them. Less than a half (42.37%) had received their first dose of IPTp. In bivariate as well as multivariate analysis, only higher level of knowledge was significantly associated with uptake of first IPTp dose. Those with better knowledge of IPTp were about twice more likely to have taken their first dose of IPTp, compared to those with lower knowledge of IPTp (AOR = 1.85; 95% CI: 1.17–2.92). Conclusions: Knowledge of IPTp as well as its uptake, were sub-optimal in this study. Since knowledge of IPTp significantly predicts uptake of the first dose of IPTp, there is the need to implement health education campaigns to raise the awareness of pregnant women and their families on the need to receive and comply with it.